2017
DOI: 10.1038/s41598-017-03592-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells secretome-induced axonal outgrowth is mediated by BDNF

Abstract: Mesenchymal stem cells (MSCs) have been used for cell-based therapies in regenerative medicine, with increasing importance in central and peripheral nervous system repair. However, MSCs grafting present disadvantages, such as, a high number of cells required for transplantation and low survival rate when transplanted into the central nervous system (CNS). In line with this, MSCs secretome which present on its composition a wide range of molecules (neurotrophins, cytokines) and microvesicles, can be a solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 59 publications
6
60
1
Order By: Relevance
“…42,43 In the present study, rats treated with WJ-MSCs showed better results than rats treated with LEV. 42,43 In the present study, rats treated with WJ-MSCs showed better results than rats treated with LEV.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…42,43 In the present study, rats treated with WJ-MSCs showed better results than rats treated with LEV. 42,43 In the present study, rats treated with WJ-MSCs showed better results than rats treated with LEV.…”
Section: Discussionsupporting
confidence: 52%
“…[57] MSCs administration after MCAO in rats resulted in reduction in infarction volume, improvement in behavioral and functional performance, and increase in GDNF and BDNF levels in the infarcted cerebral hemisphere. 42,43 In the present study, rats treated with WJ-MSCs showed better results than rats treated with LEV. This can be attributed to the contradictory effects of MSCs and LEV on the expression of the iNOS protein as the WJ-MSCs decreased its expression, while LEV increased it.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, Salgado and coworkers [82] pointed out that the secretome from WJ-MSCs and HUCPVCs is also able to increase survival, proliferation, and differentiation of hippocampal neurons due to the presence of, for example, NGF and FGF [82,83]. Additionally, the BDNF present on these cell secretomes is mediating axonal growth [84]. Figure 2 highlights ASC secretome composition, referring to specific biofactors and their biologic effect on the nervous system.…”
Section: Secretome Compositionmentioning
confidence: 99%
“…What is more, they correlate the nerve survival and outgrowth improvement with BDNF activity from co-culture experiments (Crigler et al, 2006). Further studies reveal that BDNF is a key factor secreted by MSCs from Wharton's Jelly of the umbilical cord (WJ-MSCs), which exclusively mediates axonal elongation in the rat cortical and hippocampal neurons (Martins et al, 2017).…”
Section: Neuroprotectionmentioning
confidence: 98%